2014
DOI: 10.1093/jxb/eru476
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin mediates the regulation of ABA metabolism, free-radical scavenging, and stomatal behaviour in two Malus species under drought stress

Abstract: Melatonin pre-treatment significantly increases the tolerance of both drought-tolerant Malus prunifolia and drought-sensitive M. hupehensis plants. Its beneficial effects include better water conservation in leaves, less electrolyte leakage, steady chlorophyll contents, and greater photosynthetic performance under stress conditions. Melatonin selectively down-regulates MdNCED3, an abscisic acid (ABA) synthesis gene, and up-regulates its catabolic genes, MdCYP707A1 and MdCYP707A2, thereby reducing ABA contents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
279
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 432 publications
(309 citation statements)
references
References 72 publications
26
279
1
3
Order By: Relevance
“…This finding verifies that melatonin enrichment of seeds significantly inhibited oxidative damage to membrane under PQ-generated stress. A similar effect was observed under drought stress in Malus species pre-treated with melatonin (Li et al, 2015). According to these authors, water status can be improved by dual protective mechanisms (reduced contents of both ABA and H 2 O 2 ) working synergistically to improve stomata functioning.…”
Section: Discussionsupporting
confidence: 70%
“…This finding verifies that melatonin enrichment of seeds significantly inhibited oxidative damage to membrane under PQ-generated stress. A similar effect was observed under drought stress in Malus species pre-treated with melatonin (Li et al, 2015). According to these authors, water status can be improved by dual protective mechanisms (reduced contents of both ABA and H 2 O 2 ) working synergistically to improve stomata functioning.…”
Section: Discussionsupporting
confidence: 70%
“…A recent study from Li et al (2015) showed that melatonin treatment significantly up-regulated abscisic acid (ABA) catabolism genes and down-regulated ABA biosynthesis genes in cucumber and apple, respectively, resulting in a rapid decrease of ABA content. As is known to us, lower abscisic acid (ABA) content can result in delaying the ripening process of grapes and thus prevent the normal accumulation of anthocyanin content.…”
Section: Effect Of Melatonin Treatment On Individual Anthocyanin Phenmentioning
confidence: 99%
“…This results in decreased apoptosis, improved metabolic status, and an elevated survival rate of cultured cells, unicellular organisms, animals, and plants, which suffer with oxidative stress [37,38,39,40,41,42,43,44,45]. The mechanisms of melatonin as a mitochondrial protector not only relate to its excellent free radical scavenging capacity but also to its function as a signaling molecule to upregulate gene expression of antioxidant enzymes [46,47,48] and a spectrum of stress responsive genes [49,50,51,52,53,54,55,56]. In addition, melatonin acts on the mitochondrial specific proteins such as uncoupling proteins (UCPs) to dissipate the proton gradient across the inner membrane of the mitochondria to moderately reduce the inner membrane potential [57,58,59,60].…”
Section: Introductionmentioning
confidence: 99%